KEPASTIAN YURIDIS PANCASILA SEBAGAI STAATSFUNDAMENTALNORM DALAM NEGARA HUKUM REPUBLIK INDONESIA - Diyaul Hakki; Abid Zamzami; Noorhuda Muchsin (Fakultas Hukum Universitas Islam Malang, 2022)
ABSTRACT After Indonesia's independence, there were various interpretations of juridical certainty and the position of Pancasila, both in the form of understanding that Pancasila is part of the Constitution and understanding that Pancasila is another higher part of the Constitution. The formulation of the problem in this study is 1. How is the juridical certainty of the position of Pancasila as a staatsfundamentalnorm in the Hierarchy Law in Indonesia? and 2. How is the Legis Ratio of Pancasila's position as a staatsfundamental norm in the theory of Legal Science? By conducting a normative study and the approach to legislation (Statue Approach), Conceptual Approach (Conceptual Approach), and Historical Approach (Historical Approach), as well as by using primary and secondary legal materials. The results show that the juridical position of Pancasila can be interpreted from the word